Pengaruh Gelombang Mikro Pada Pretreatment Tongkol Jagung Menjadi Bioetanol - Imron Sutiono; Chairul Chairul; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Oil production is predicted  decreasing until 20 billion barrels in  2050. The decreasing of oil production will cause efforts to find alternative renewable and   friendly source energy. The one of alternative energy is bioetanol that produced from biomass waste. The Micro wace radiation will give to corn cob as a pretreatment process in this research. Micro wave is expected to break lignin structure in order to get the optimum of etanol. The purpose of the research is to know the effect of micro wave in the pretreatment of corn cob. The corn cob will radiate  on 180 watt through micro wave  with time variation 2,4,6,8 dan 10 minutes, then continued with hidrolisis process using dilute H2SO4 and fermentation process using Saccharomyces cerevisiae. The result of fermentation will analyzed  with Guymon method by using alcoholmeter. The results indicate the highest concentration of bioetanol that  get  from this fermentation process up to 2,5% (25g/l) during 24 hours for the variation micro wave radiation in 6 minutes. The optimum Yield of bioetanol up to 23,67%. The longer time fermentation process and the longer radiation of microwave that is done in this research show that there is no increasing the concentration of bioetanol that we get.  Key word : bioetanol. Microwave, corn cob, Saccharomyces Cerevisiae